2016
DOI: 10.1007/s11748-016-0691-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of patent false lumen of the aortic arch after hemiarch replacement

Abstract: Brachiocephalic artery dissection and no tear resection are potential predictors of patent false lumen of the aortic arch after hemiarch replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…На протяжении многих лет стандартным подходом являлся принцип «primary tear oriented», который предполагает резекцию проксимальной фенестрации и протезирование восходящего отдела аорты по методике открытого дистального анастомоза или протезирования полудуги аорты [9,10]. Однако в настоящее время уже известно, что несмотря на успешное выполнение операции на проксимальных отделах аорты, проходимый ложный канал дистальнее первичной реконструкции сохраняется у 64-90% пациентов, что оказывает крайне неблагоприятное влияние на отдаленные результаты лечения [10][11][12][13][14][15]. Также известно, что одним из ключевых факторов, препятствующих развитию тотального тромбоза ложного канала, являются так называемые резидуальные фенестрации (включающие как дистальные, так и проксимальные, которые не были ликвидированы при первичном хирургическом лечении) [16].…”
Section: Discussionunclassified
“…На протяжении многих лет стандартным подходом являлся принцип «primary tear oriented», который предполагает резекцию проксимальной фенестрации и протезирование восходящего отдела аорты по методике открытого дистального анастомоза или протезирования полудуги аорты [9,10]. Однако в настоящее время уже известно, что несмотря на успешное выполнение операции на проксимальных отделах аорты, проходимый ложный канал дистальнее первичной реконструкции сохраняется у 64-90% пациентов, что оказывает крайне неблагоприятное влияние на отдаленные результаты лечения [10][11][12][13][14][15]. Также известно, что одним из ключевых факторов, препятствующих развитию тотального тромбоза ложного канала, являются так называемые резидуальные фенестрации (включающие как дистальные, так и проксимальные, которые не были ликвидированы при первичном хирургическом лечении) [16].…”
Section: Discussionunclassified
“…recent development of MDCT has allowed detailed evaluations to determine whether the brachiocephalic branches are involved in a dissection. 22 When a brachiocephalic branch is dissected, the branch has a double-barrel lumen, and there has to be a re-entry on the distal side of the branch, although the re-entry often cannot be detected because it is outside of the CT scan range. Patients who have a DeBakey type I aortic dissection usually have several secondary tears in the descending aorta or near the visceral aortic branches; however, such tears have a minimal effect on the patency of the aortic arch false lumen.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have mentioned that patent FLs and non-resection of primary entries are potential predictors of late aortic dilatation. 1 , 4 , 5 ) In previous AAAD cases, an intimal tear has been found in the ascending aorta in more than 60%, arch in 13%–30%, and descending aorta in 6% of cases. Additionally, multiple tears have been found in 8%–10% of cases, whereas 3% of cases have not shown any tear.…”
Section: Discussionmentioning
confidence: 96%
“…Such dilatation after AAAD repair has been reported to occur in approximately 40% of patients. 1 , 4 ) Kimura et al have reported that the rate of surgical reintervention (involving thoracic endovascular aneurysm repair) to the aortic arch after AAAD repair is 7.8%, 5 ) and Preventza et al have reported that the mortality rate of traditional open surgery is 11.7%. 3 ) In practice, distal dilatation can cause many problems, which may result in inoperable as well as sudden death cases associated with aortic events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation